Construção e validação de escala de autoeficácia dos pais sobre o sono infantil - Jespersen, Tamires Rebeca Forte Viana (2022)
Parental self-efficacy in understanding infant sleep behavior is a variable that can prevent the emergence of more serious problems in the child's development. We aimed to construct and validate an evaluative scale of parental self-efficacy in identifying infant sleep behavior up to two years of age. A methodological study based on the steps recommended by psychometrics and using the construct of self-efficacy. An integrative review was conducted to identify the parents' habits that influence the child's sleep, creating an initial scale with 32 Likert-type items. This was subjected to two content assessments electronically at two separate times by six and three judges respectively, selected by criteria adapted from Jasper (1994) between the months of October and November 2020. The criteria evaluated were Behavior, Simplicity, Clarity, Relevance, Accuracy, Modality, and Typicity. Then, the scale items were semantically validated for clarity, relevance, and location in the dimensions with 30 participants, mothers/caregivers of children up to two years of age in the period from March to June 2021 through an interview at the Specialized Pediatric Outpatient Clinic of the Federal University of Ceará (UFC-in Portuguese). Content validity obtained by content validity index (CVI) with CVI ≥0.78 excellent; also, Binominal Exact Test and Kappa were used. After semantical validation, the scale was applied to 161 mothers/caregivers of children up to two years old by means of interviews at the mentioned outpatient clinic and at the Family Development Coordination Office (CDFAM- in Portuguese) between the months of August and November 2021 and in July 2022. Judges and target population signed the Informed Consent Form according to Resolution No. 466/12. Study approved with CAAE number 19291219,9,0000,5054. In the first content analysis, the total CVI of the scale was 0.90 and 4 items were excluded. In the second analysis, the scale's total CVI was 1.00 and items were adjusted. In the semantic analysis, items 16 and 24 showed less clarity (70% and 76.7% respectively) but were considered important (90%). In the analytical pole, six items were excluded from the final version. Another three items were indicated for exclusion; however, they were kept because of the subsidies identified in the literature review. The final scale showed a three-dimensional model with an overall Cronbach's alpha of 0.83 and McDonald's Omega of 0.77. The answers "I can do it most of the time" and "I can always do it" predominated among the participants. The scale was called the "Parental Self-Efficacy Scale on Infant Sleep Behavior" with 18 items. The technology will allow nurses to assess the confidence of primary caregivers and identify difficulties in developing or implementing infant sleep routines and habits. This will guide the actions and care in the nursing consultation, favoring the promotion of infant sleep and holistic care.